2005
DOI: 10.1124/mol.105.015966
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Drug Binding Site on Voltage-Gated Sodium Channels in Rat Brain

Abstract: The effectiveness of several antiepileptic, analgesic, and neuroprotective drugs is attributable to state-dependent inhibition of voltage-gated sodium channels. To help characterize their site and mode of action on sodium channels, a member of the lamotrigine family,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Moreover, point mutations of the external residues (e.g., in the external part of D4S6 or in the D4 external pore loop, the latter being equivalent to W1716 in Na v 1.2) would significantly alter the access of external QX-314 and local anesthetics binding to the channel pore (Ragsdale et al, 1994;Qu et al, 1995;Wang et al, 1998;Lee et al, 2001;Tsang et al, 2005). Binding assays of [ 3 H]BW202W92 of the lamotrigine family also support an external binding site for the anticonvulsants (Riddall et al, 2006). Most intriguingly, occupancy of the external pore mouth of Na + channels by external Na + would delicately alter the local geometry to make diclofenac (a structural analogue of carbamazepine and also an inactivation stabilizer of the channel) an opportunistic blocker of the pore (Yang and Kuo, 2005).…”
Section: Two-electrode Intracellular Recordingmentioning
confidence: 93%
“…Moreover, point mutations of the external residues (e.g., in the external part of D4S6 or in the D4 external pore loop, the latter being equivalent to W1716 in Na v 1.2) would significantly alter the access of external QX-314 and local anesthetics binding to the channel pore (Ragsdale et al, 1994;Qu et al, 1995;Wang et al, 1998;Lee et al, 2001;Tsang et al, 2005). Binding assays of [ 3 H]BW202W92 of the lamotrigine family also support an external binding site for the anticonvulsants (Riddall et al, 2006). Most intriguingly, occupancy of the external pore mouth of Na + channels by external Na + would delicately alter the local geometry to make diclofenac (a structural analogue of carbamazepine and also an inactivation stabilizer of the channel) an opportunistic blocker of the pore (Yang and Kuo, 2005).…”
Section: Two-electrode Intracellular Recordingmentioning
confidence: 93%
“…Previous studies indicated that activation of PKC sensitizes TRPV1 responses (Cesare and McNaughton 1996;Premkumar and Ahern 2000;Riddall et al 2006). For this reason we tested two different PKC antagonists, 20 M sphingosine and 1 M BIM, on their ability to modulate responses to capsaicin in anisotonic conditions.…”
Section: Modulators Of Capsaicin's Responses To Changes In Tonicitymentioning
confidence: 99%
“…This profile is similar to the antiepileptic drugs carbamazepine (CBZ), lamotrigine (LTG), and DPH, all of which are selective for the former experimental seizure model over the latter (Miller et al, 1986;Lang et al, 1993;Meldrum, 2002). It is now generally accepted that CBZ, LTG, and DPH share a common primary mode of action (although postulated novel molecular target sites may contribute to the distinct pharmacological profiles of the drugs in different cellular compartments; Cunningham and Jones, 2000;Poolos et al, 2002;Riddall et al, 2006) in altering fast inactivation gating of voltage-gated sodium channels (Willow et al, 1985;Lang et al, 1993;Ragsdale et al, 1996), producing tonic and use-dependent blockade.…”
mentioning
confidence: 99%